Pengembangan Kecerdasan Jamak Pada Anak Usia Dini (PIAUD IAIN Kudus, 2016)
Multiple intelligences development in early childhood is a learning process that will be developed by early childhood educators in the implementation of learning educators who want to teach a subject matter, then the educators to teach in accordance with the trend of learning styles of learners. Because in one classroom there are some students who each have different intelligences. This research on multiple intelligence development in early childhood. The purpose of this study were (1) to determine the definition of multiple intelligences; (2) to determine the types of multiple intelligences; (3) to implement learning activities focused on the development of intelligence plural (multiple intelligences). This paper use a qualitative approach (library research). It try to gain an understanding of the holistic about the problems being faced by the reality (Sugiyono (2010: 1). The method of this study appeared as a paradigm shift in looking at reality or phenomena or symptoms. Every school should be able to develop intelligence potential of each child. Paradigm of intelligence and child's success is only assessed on IQ or mark, whereas the concept of multiple intelligences is, Howard Gardner argues that each student is intelligent. And intelligence is not just one, but plural. The type rather than the multiple intelligences include, among others: (1) Intelligence of logic or mathematics is the intelligence in terms of numbers and logic. ; (2) The language or linguistic intelligence is the intelligence of word processing, or the ability to use words effectively both orally and in writing. ; (3) visual-spatial intelligence is one part of the plural intelligence which is closely linked to the ability to visualize images; (4) musical intelligence is the ability to handle musical forms; (5) Physical intelligence is an intelligence which currently use are capable of doing great movements, such as running, dancing .; (6) The naturalist intelligence is the expertise to identify and categorize the species (flora and fauna) in the surrounding neighborhood .; (7) intrapersonal intelligence is the ability of ourselves to think reflectively; (8) Interpersonal intelligence is to think by communicating with others; (9) an existential intelligence is the ability to feel and appreciate the variety of spiritual experiences on the appropriate lesson or understanding of faith in God.